Comparison of the Anti-Plaque Effect of Miswak (Salvadora Persica) and Dandasa (Juglan Regia) on gingival health - Haseeb Pervaiz, Shahbaz Ahmed, Fizza Khalid, Sania Riaz, Sumaiya Shabbir, Aisha Haseeb, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Anti-bacterial effect of Miswak on microorganism has already been proven in previous researches. The Dandasa is used by most women in Saudi Arabia, India and Pakistan as a toothbrush for cleaning the teeth. Aim: This study was done for the comparison between the effect of Miswak and Dandasa in improving gingival health, as both has anti-plaque action and absence of plaque is directly proportional to gingival health. Methods: A prospective cohort study was carried out at the Department of Periodontology, Dr.Ishrat-ul-Ebad Khan Institute of Oral Health Sciences, Karachi for a period of 6 months. Total 90 patients fulfilling the inclusion criteria were included into two Groups. In group-A habitual user of miswak were taken and in group-B habitual user of dandasa were taken. The Plaque score and gingival index were made zero before the start of observation by conducting ultrasonic scaling. Results: In Group A 57.8% participants were using miswak once a day and 42.2% twice a day. In group B 44.4% participants were using Dandasa once a day 44.2% and 55.6% twice a day. Mean post-gingival index score was 1.95±0.52 in group A and 1.08±0.28 in group B. Mean post plaque index score in Group A was 1.97±0.69 and Group B was 1.15±0.36. The results portrayed significant discrepancy in pre and post gingival index. The conclusion also depicted prominent variability in pre-post-plaque index. Both indices showed that the dandasa was better at plaque control as compare to Miswak Conclusion: Mean Gingival Index (GI) and Plaque Index (PI) scores in dandasa group was prominently less as compared to Miswak group. Keywords: Gingival Index, Plaque index, Dandasa, Miswak